IMPACT OF COVID-19 ON LIQUIDITY OF THE BANKING SECTOR OF PAKISTAN - Muhammad Umair Ali; Saliha Gul Abbasi; Faraz Ahmad Abbasi; Mazhar Abbas; Shakeel Sarwar; Owais Shafiqu; Ghulam Dastgeer (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The 33 banks of Pakistan’s banking sector were tested using different stressed testing techniques already used in researches are renowned in world of finance to stress test any financial institutions. The results of Stress testing suggest that only Faysal Bank and Standard Chartered Bank are secured banks in terms of stable liquidity outlook. All other banks except foreign banks are vulnerable to small liquidity shocks. Moreover, most of the banks have very low Liquidity Coverage ratio showing the clear asset liability mismatch in short run. The test is run on the Balance sheet data of December 31, 2020.